La diversification des trajectoires de métropolisation au sud du Vietnam - Khac Minh Tran (EchoGéo)
Since the Doi Moi (Renovation) reforms initiated in 1986, Ho Chi Minh City (HCMC) and the neighbouring provinces have played a fundamental role in the economic development of Vietnam. Among the neighbouring provinces, that are historically considered as the hinterland of HCMC, Binh Duong is nowadays emerging as a new metropolitan pole. The rapid development of HCMC and Binh Duong is commonly based on a globalized industrialization, which leads to the creation of multiple industrial parks, and an emerging real estate sector, profoundly transforming the local landscape and economic structure. These two provinces have adopted specific industrial and urban strategies in order to strengthen their competitiveness. In parallel with the diversification of urban and economic trajectories, new transprovincial dynamics of complementarity, cooperation and competition appear and redefine in depth the South Vietnam’s regional development